STRENGTHENING THE POSITION OF IMMIGRATION POLICIES IN THE PREVENTION OF TRADE CRIMINAL ACTIONS AND HUMAN STUNNING - Felix Ferdin Bakker; Muh. Alif Jamil Pratama (Journal of Law and Border Protection, 2020)
Transnational crime in the territory of Indonesia is increasingly motivated by several pushes and pull factors. First, Indonesia's strategic position makes many people tempted to anchor to Indonesia to make Indonesia a transit country and live and develop. This is worrying because it cannot be denied that foreigners enter a country in an illegal way and cross borders. Second, state borders without immigration documents or other valid documents will create new problems, which of course, can lead to criminal issues. Of course, a policy of equitable borders and controls is the answer to this problem.Another thing that cannot be left out is that establishing a positive law that is firm and binding is the key to the success of this policy. This research study uses normative legal research methods with qualitative data collection juxtaposed with descriptive analysis techniques so that the existing problems regarding transnational crimes, especially human smuggling, can be presented comprehensively and informatively. Outreach to the community as the first informant is one of the keys to community-based surveillance and enforcement management. It is hoped that with the coordination and synergy of problems related to foreign nationals who are the perpetrators of human smuggling crimes, it is expected that it can decrease statistically so that the selective policy principle that is aspired is that only foreigners who provide benefits and have valid documents can enter Indonesian territory and give services to Indonesia's national progress.